2015
DOI: 10.1186/s12935-015-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of long non-coding RNA DLX6-AS1 in lung adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LAC), the primary histological type of non-small cell lung cancer (NSCLC), has displayed an increasing incidence and mortality worldwide. However, therapeutic approaches were limited. Dysregulation of some lncRNAs has been shown in various types of cancers including LAC. The aim of the present study was to vertify lncRNA DLX6-AS1 expression in LAC.MethodsMicroarray assay revealed expression profile of lncRNAs in LAC. qRT-PCR ( quantitative reverse transcription PCR) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 50 publications
2
58
1
Order By: Relevance
“…Most DLX family members play a role in cancer. For example, DLX6 and DLX5 are up‐regulated in metastatic breast cancer cells in lung and bone, and the DLX4 isoform β protein 1 (BP1) is correlated with a poor prognosis in patients with breast cancer . Surprisingly, in the current study, IHC using the polyclonal antibody against DLX6 revealed DLX6 expression in both epithelial cells and myoepithelial cells; thus, we cannot assume that this DLX6 antibody is a specific marker for E‐ACC.…”
Section: Discussioncontrasting
confidence: 68%
“…Most DLX family members play a role in cancer. For example, DLX6 and DLX5 are up‐regulated in metastatic breast cancer cells in lung and bone, and the DLX4 isoform β protein 1 (BP1) is correlated with a poor prognosis in patients with breast cancer . Surprisingly, in the current study, IHC using the polyclonal antibody against DLX6 revealed DLX6 expression in both epithelial cells and myoepithelial cells; thus, we cannot assume that this DLX6 antibody is a specific marker for E‐ACC.…”
Section: Discussioncontrasting
confidence: 68%
“…Down-regulation of lncRNA DLX6-AS1 expression decreased the DLX6 mRNA and protein levels. 13 However, the role of DLX6-AS1 in renal cell cancer is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we predicted that LncRNA DLX6-AS1 could regulate the expressions of FSCN1, SOX11 and PSAT1 through competitive binding to hsa-miR-145. It has been reported that lncRNA DLX6-AS1 was up-regulated in lung adenocarcinoma (LAC) tissues compared to paired adjacent normal lung tissues and high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage [41]. Recent researches have demonstrated that FSCN1, SOX11 and PSAT1 were associated with poor clinical outcome in breast cancer [42][43][44].…”
Section: Discussionmentioning
confidence: 99%